2009
DOI: 10.1136/bmj.b2030
|View full text |Cite
|
Sign up to set email alerts
|

Self administered cognitive screening test (TYM) for detection of Alzheimer's disease: cross sectional study

Abstract: Objective To evaluate a cognitive test, the TYM (“test your memory”), in the detection of Alzheimer’s disease.Design Cross sectional study.Setting Outpatient departments in three hospitals, including a memory clinic.Participants 540 control participants aged 18-95 and 139 patients attending a memory clinic with dementia/amnestic mild cognitive impairment.Intervention Cognitive test designed to use minimal operator time and to be suitable for non-specialist use.Main outcome measures Performance of normal contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
193
4
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(217 citation statements)
references
References 32 publications
12
193
4
6
Order By: Relevance
“…Indeed, patients with AD have been found to perform more poorly than other demented patients on the items ''recall of 3 words'' and ''orientation to time'' while those with vascular dementia did more poorly on items of attention. 23 However, Brown et al 22 found that the MMSE could only detect a low 52% of their patients with AD. Furthermore, frontal patients typically suffer more from problems with executive functioning (EF), an aspect of cognition that is underrepresented in the test.…”
Section: Populations It Has Been Used Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, patients with AD have been found to perform more poorly than other demented patients on the items ''recall of 3 words'' and ''orientation to time'' while those with vascular dementia did more poorly on items of attention. 23 However, Brown et al 22 found that the MMSE could only detect a low 52% of their patients with AD. Furthermore, frontal patients typically suffer more from problems with executive functioning (EF), an aspect of cognition that is underrepresented in the test.…”
Section: Populations It Has Been Used Inmentioning
confidence: 99%
“…Due to the fact that the MMSE is memory-and languageoriented, it has a bias toward temporal and parietal lobe functioning 22 and as such should be more sensitive in patients with degeneration and/or lesions in these areas. Indeed, patients with AD have been found to perform more poorly than other demented patients on the items ''recall of 3 words'' and ''orientation to time'' while those with vascular dementia did more poorly on items of attention.…”
Section: Populations It Has Been Used Inmentioning
confidence: 99%
“…The groups in this study were classified in a similar fashion with MMSE scores as a reference base. The MMSE scores for each group are: Control (28)(29)(30), MCI (26-29/MoCA < 26 and > 20), Early AD (23)(24)(25)(26), mild to moderate AD (18)(19)(20)(21)(22), moderate to severe AD (11)(12)(13)(14)(15)(16)(17)(18), and severe AD (< 10), respectively.…”
Section: Participantsmentioning
confidence: 99%
“…Differentiation of other forms of dementia with distinct neurocognitive patterns (Diffuse Lewy Body Disease, Subcortical Vascular Dementia, Frontal Lobe Dementia) from AD within patients presenting with memory complaints is of particular interest to researchers [18] as well as clinicians [19,20]. Brief screening instruments have been developed with acceptable levels of sensitivity and specificity [21][22][23][24][25][26]. However, prior studies suggest that improvements in the practical application and interpretation of these instruments will aid in their usefulness in both specialty clinics and primary care setting [7].…”
Section: Introductionmentioning
confidence: 99%
“…Screening measures such as the Mini-Mental Status Examination (MMSE) are particularly insensitive to distinguishing MCI from normal controls or those with AD (Mitchell, 2009). Other tools such as the Montreal Cognitive Assessment (Nasreddine et al, 2005), Test Your Memory (TYM) (Brown et al, 2009) and telephone screening batteries (Manly et al, 2011;Hill et al, 2005) require a trained administrator or clinician and provide only a global score without information on specific profiles of deficits across different cognitive domains.…”
Section: Introductionmentioning
confidence: 99%